2012
DOI: 10.1074/jbc.a111.275370
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids sensitize the innate immune system through regulation of the NLRP3 inflammasome.

Abstract: PAGES 38708 and 38709:It has come to our attention that errors were made during the preparation of Figs. 2 and 3. Incorrect Western blot images for the induction of NLRP3 (Fig. 2, A and B) and the actin loading control (Fig. 3B) were inserted inadvertently. These mistakes did not influence the primary conclusions of our studies. The correct blots are now shown. We apologize for any inconvenience this error may have caused..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…Thus, it is conceivable that the regulatory network delineated in this study is part of a neuroendocrine-immune axis, whereby stress-induced elevation of the steroid hormone 20E drives elevated PGRP-LC expression and primes all the AMP genes, enabling a more robust immune response during times of stress. Although the direction of this regulation is opposite of that observed in mammals, where stress-induced glucocorticoids are best known to pharmacologically reduce the inflammatory response, several recent reports have clearly shown that glucocorticoids, when produced at physiological levels, actually induce the expression of innate immune receptors like TLR2 and NLRP3 (Shuto et al, 2002;Hermoso et al, 2004;Sakai et al, 2004;Busillo et al, 2011), very similar to the 20E-PGRP-LC axis demonstrated here. Thus, a profound but poorly understood conservation in the neuroendocrine regulation of innate immunity may exist in invertebrates and mammals.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, it is conceivable that the regulatory network delineated in this study is part of a neuroendocrine-immune axis, whereby stress-induced elevation of the steroid hormone 20E drives elevated PGRP-LC expression and primes all the AMP genes, enabling a more robust immune response during times of stress. Although the direction of this regulation is opposite of that observed in mammals, where stress-induced glucocorticoids are best known to pharmacologically reduce the inflammatory response, several recent reports have clearly shown that glucocorticoids, when produced at physiological levels, actually induce the expression of innate immune receptors like TLR2 and NLRP3 (Shuto et al, 2002;Hermoso et al, 2004;Sakai et al, 2004;Busillo et al, 2011), very similar to the 20E-PGRP-LC axis demonstrated here. Thus, a profound but poorly understood conservation in the neuroendocrine regulation of innate immunity may exist in invertebrates and mammals.…”
Section: Discussionsupporting
confidence: 65%
“…In the context of immunity, pharmacologic application of glucocorticoids has multiple potent anti-inflammatory effects on immune cells (Necela and Cidlowski, 2004;Sternberg, 2006). In addition to the well-known immunosuppressive effects of glucocorticoids, many studies have revealed that physiological levels of glucocorticoids actually enhance the immune and inflammatory response (Galon et al, 2002;Shuto et al, 2002;Goulding, 2004;Hermoso et al, 2004;Sakai et al, 2004;Dhabhar, 2009;Busillo et al, 2011). Several other nuclear hormone receptors, including estrogen receptors (ERs), peroxisome proliferatoractivated receptors (PPARs), vitamin D receptors (VDRs), retinoid-related orphan receptors (RORs), retinoid X receptors (RXRs) and liver X receptors (LXRs), have also been found to positively regulate innate immunity and proinflammatory cytokine expression (Tontonoz et al, 1998;Hong and Tontonoz, 2008;Jetten, 2009;Baeke et al, 2010;Nunez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, glucocorticoids are the main neuroendocrine to regulate the immune system (45). Several studies showed that stressors can rapidly result in the systemic release of glucocorticoids, and thereby alter the mammalian innate immune and inflammatory response through the glucocorticoid receptor (44,46,47). In insects, molting hormone 20E titers can also increase when they are exposed to different stressors, such as starvation, heat treatment, and sleep deprivation (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…4; Table S4), which may allow early colonization and adaptation of these probiotics to the host. GR signaling leads to enhanced release of proinflammatory cytokines IL-1β, TNF-α, and IL-6, 54 hence, it may be conceivable that downregulation of GR signaling at an early stage by both LA and LGG could suppress the initial host response that otherwise prevents probiotic colonization (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%